Titanium particle reinforced magnesium-based composite material with good plasticity and preparation method thereof
By using a preheated shear stirrer and specific stirring treatment during the preparation process of magnesium-based composite materials, combined with homogenization treatment and hot extrusion molding, the uneven distribution of titanium particles and oxides, gases, and inclusions are solved. problem, significantly improving the mechanical properties of magnesium-based composites.
Patent Information
- Application Number
- CN202411457741.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, titanium particles have uneven distribution when strengthening magnesium-based composite materials, and there are many oxides, gases and inclusions generated by ordinary mechanical stirring, resulting in poor performance of magnesium-based composite materials.
Using a preheated shear mixer, the preheated titanium particles are quickly added to the magnesium melt and specific stirring is performed, combined with homogenization treatment and hot extrusion molding to ensure that the titanium particles are in the magnesium matrix. Evenly distributed.
It effectively improves the settlement problem of titanium particles in the magnesium matrix, achieves uniform dispersion of titanium particles, and improves the comprehensive mechanical properties of magnesium-based composite materials. The tensile strength reaches 222MPa, the yield strength is 151MPa, and the elongation is 21%.
Smart Images

Figure CN119332122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy materials, and in particular relates to a titanium particle-reinforced magnesium-based composite material with good plasticity and a preparation method thereof. Background Art
[0002] Lightweight magnesium has extremely low density, good machinability and structural properties, and has broad application prospects in the military, automotive, and aerospace fields. However, there are still bottlenecks in the practical application of magnesium, which is due to the low strength of magnesium alloys and the poor plasticity at room temperature, which makes processing difficult. Studies have shown that adding particle reinforcements to magnesium to form composite materials can effectively improve the above shortcomings.
[0003] Common particle reinforcements include carbides, oxides, borides and pure metals. However, the addition of particle reinforcements is likely to cause voids in cast magnesium-based composites, leading to cracks. Several common reinforcements such as ceramic nanoparticles have low wettability with the molten magnesium matrix and are difficult to disperse. Metal particles such as Cu, Ni, Fe and Ti have high strength, high ductility and excellent elastic modulus. Among them, Ti particles almost never react with Mg to form hard or non-deformable intermetallic compounds, and have the same crystal structure as Mg at room temperature, with good wettability. Using them as reinforcements can prepare magnesium-based composites with both high strength and high plasticity.
[0004] Stirring casting is a traditional method for preparing magnesium-based composites reinforced with titanium particles. However, in order to fully mix the solution, ordinary stirring methods will form vortices on the melt surface during the stirring process, and oxides and inclusions will be brought into the melt while introducing gases. At the same time, the density difference between titanium particles and magnesium alloys is large, and the sedimentation of titanium particles is very serious. They are very easy to agglomerate together and are unevenly distributed, which will reduce the comprehensive mechanical properties of magnesium-based composites. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the main purpose of the present invention is to provide a magnesium-based composite material reinforced with titanium particles having good plasticity and a preparation method thereof, aiming to solve the problem that the existing metal titanium particles are unevenly distributed when reinforcing the magnesium-based composite material, and a large amount of oxides, gases and inclusions generated due to ordinary mechanical stirring, which leads to poor performance of the magnesium-based composite material reinforced with titanium particles.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a magnesium-based composite material reinforced with titanium particles having good plasticity, comprising the following steps: 1) liquid casting molding: placing a magnesium matrix in a crucible, introducing a protective gas, heating to form a liquid magnesium melt, and keeping the temperature; quickly adding preheated titanium particles into the liquid magnesium melt, stirring with a preheated shear force stirrer, and then quickly water cooling to obtain a cast composite material;
[0008] 2) homogenization treatment: subjecting the as-cast composite material in step 1) to solution treatment at 150-250° C. for 6-18 h;
[0009] 3) hot extrusion molding: preheating the cast composite material that has been homogenized in step 2) and then hot extruding it to obtain a magnesium-based composite material reinforced with titanium particles;
[0010] Among them, in step 1), the preheated titanium particles are quickly added to the magnesium melt, and the stirring conditions of the preheated shear stirrer are: first, stir at a speed of 100-300 rpm, which is consistent with the speed of the stirring head, increase the speed to 1000-1400 rpm and stir for 4-10 minutes, and during the stirring process, the position of the stirring head in the magnesium melt is fixed, and the bottom end of the stirring head is 10-50 mm away from the bottom of the crucible.
[0011] In some specific embodiments, the mass ratio of the magnesium matrix to the titanium particles is 97-99:1-3.
[0012] In some specific embodiments, the temperature of the liquid magnesium melt is 680-730°C.
[0013] In some specific embodiments, the particle size of the titanium particles is no greater than 20 μm.
[0014] In some specific embodiments, the preheating parameters of the titanium particles are: preheating temperature is 200-300° C., and preheating time is 20-40 min.
[0015] In certain specific embodiments, the preheating conditions of the shear force agitator in step 1) are: preheating temperature is 600-700° C., and preheating time is 30-60 min.
[0016] In some specific embodiments, the protective gas in step 1) is a mixed gas of carbon dioxide and sulfur hexafluoride in a mass ratio of 1:99.
[0017] In some specific embodiments, the extrusion molding conditions in step 3) are: preheating temperature of 300-400°C, preheating time of 0.5-1.5h, extrusion temperature of 280-400°C, extrusion ratio of 25:1, and extrusion speed of 0.5-1m / s.
[0018] The present invention also provides a titanium particle reinforced magnesium-based composite material with good plasticity obtained by the above-mentioned preparation method. The magnesium-based composite material has a tensile strength of 222 MPa, a yield strength of 151 MPa, and an elongation of 21%.
[0019] Compared with the prior art, the present invention has at least the following advantages:
[0020] 1) The preparation method of the titanium particle reinforced magnesium-based composite material provided by the present invention effectively improves the sedimentation problem of metal titanium particles in the magnesium matrix, and at the same time enables the metal titanium particles to be evenly dispersed in the magnesium matrix, thereby improving the comprehensive mechanical properties of the composite material; 1) The method adopts a preheated shear force agitator, and the stirring speed is changed in real time to match the state of the magnesium melt (first, stirring at a speed of 100-200 rpm to be consistent with the speed of the stirring head, and then the speed is increased to 1000-1400 rpm and stirred for 4-10 minutes, and the position of the stirring head in the magnesium melt is fixed during the stirring process, and the bottom end of the stirring head is 10-50 mm away from the bottom of the crucible).
[0021] 2) The preparation method of the titanium particle reinforced magnesium-based composite material provided by the present invention adopts a specific shear force agitator to prevent the upper surface of the magnesium melt from generating vortices during the stirring process, thereby preventing more oxides, gases, and inclusions from being drawn into the melt, so that the metal titanium particles can be evenly dispersed without being drawn into the gas to form too many defects. This effectively improves the quality of the melt and the comprehensive mechanical properties of the magnesium-based composite material.
[0022] 3) The preparation method provided by the present invention has a simple and easy-to-control stirring process, and can ultimately obtain a magnesium-based composite material with uniformly distributed metal titanium particles, no microscopic agglomeration, and fewer slag inclusion defects. The obtained magnesium-based composite material has higher strength and plasticity than the magnesium matrix, wherein the tensile strength can reach 222 MPa, the yield strength can reach 151 MPa, and the elongation can reach 21%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0024] Figure 1 is a SEM image of the magnesium-based composite material in Comparative Example 1;
[0025] Figure 2 Metallographic microstructure of the magnesium-based composite material prepared in Example 1;
[0026] Figure 3 Metallographic microstructure of the magnesium-based composite material prepared in Example 2. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0028] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0029] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0030] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0031] In the following examples, the magnesium matrix is ZM61, purchased from Chongqing Yuhua New Material Technology Co., Ltd.; the protective gas carbon dioxide (CO2) and sulfur hexafluoride (SF6) are purchased from Chongqing Ruike Gas Co., Ltd., and the particle size of the metal titanium particles is ≤20 μm;
[0032] In the following embodiments, the shear force agitator is a liquid metal stirring device disclosed in patent number 202120829227.2 applied by the present applicant;
[0033] The test methods used in the following embodiments include: by testing the main properties of each test sample respectively, to reflect the dispersion performance of titanium particles in the magnesium-based composite material; the main properties tested in this application include metallographic microstructure diagrams, SEM images and mechanical properties.
[0034] 1) Mechanical properties test
[0035] Using CMT-5105 equipment, the mechanical properties of the samples were tested according to the DB / T1177-2018 method; Example 1
[0036] This embodiment provides a method for preparing a titanium particle-reinforced magnesium-based composite material with good plasticity, which comprises the following steps:
[0037] 1) Preheating titanium particles: weigh 24 g of titanium particles with a particle size of ≤20 μm and put them into a crucible, and preheat them at 200° C. for 30 min;
[0038] 2) Liquid casting: In the presence of a mixture of carbon dioxide and sulfur hexafluoride at a mass ratio of 1:99, 1012g of pure magnesium was placed in a crucible and heated to 720°C. After melting, it was kept warm for 10 minutes; the temperature was lowered to 680°C, 24g of preheated titanium particles were added, and the shear force stirrer was fixed to stir for 30s at 200rpm (at this time, the magnesium melt and the stirring head speed were consistent), and the speed was increased to 1300rpm and stirred for 270s. During the entire stirring process, the stirring head position was fixed, and the bottom end of the stirring head was 25mm away from the bottom of the crucible. After stopping stirring, it was quickly cooled with water to obtain a cast composite material.
[0039] 3) homogenization treatment: subjecting the as-cast composite material obtained in step 2) to a solution treatment at 200° C. for 12 h;
[0040] 4) Hot extrusion molding: The cast composite material after homogenization treatment in step 3) is preheated at 350°C for 1.0h, and then extruded at an extrusion temperature of 300°C, an extrusion ratio of 25:1, and an extrusion speed of 1m / s to obtain a titanium particle reinforced magnesium-based composite material.
[0041] The performance of the prepared magnesium-based composite material is tested in this application, wherein the metallographic diagram of the magnesium-based composite material is as follows: Figure 2 As shown in the figure, it can be seen that spherical titanium particles with a diameter of 5-10μm can be distributed relatively evenly in the matrix, and no obvious particle agglomeration area is observed, which is beneficial to the improvement of the comprehensive mechanical properties of magnesium-based composites.
[0042] The present application also tests the mechanical properties of the prepared magnesium-based composite material. Specifically, at room temperature, the tensile mechanical properties of the cast alloy are measured, and the tensile strength is 222MPa, the yield strength is 155MPa, and the elongation is 21.1%. Compared with the mechanical properties of Comparative Example 1 at room temperature, Mg-3%Ti p The tensile strength, yield strength and elongation of the material increased by -1.3%, -5.8% and 74.4% respectively.
[0043] Example 2
[0044] This embodiment provides a method for preparing a titanium particle-reinforced magnesium-based composite material with good plasticity, which comprises the following steps:
[0045] 1) Preheating titanium particles: weigh 30 g of titanium particles with a particle size of ≤20 μm and put them into a crucible, and preheat them at 200° C. for 30 min;
[0046] 2) Liquid casting: In the presence of a mixed gas of carbon dioxide and sulfur hexafluoride in a mass ratio of 1:99, 1060 g of pure magnesium was placed in a crucible and heated to 720°C. After melting, the mixture was kept warm for 10 min; the mixture was cooled to 680°C, 30 g of preheated titanium particles were added, and the shear force stirrer was fixed to stir the mixture. The mixture was first stirred at a speed of 300 rpm for 30 s (at this time, the speed of the magnesium melt was consistent with that of the stirring head), and then the speed was increased to 1400 rpm and stirred for 270 s. During the entire stirring process, the stirring head was fixed in position, and the bottom end of the stirring head was 15 mm from the bottom of the crucible. After stopping stirring, the mixture was rapidly cooled with water to obtain a cast composite material (the SM diagram of the cast composite material is shown in FIG. Figure 3 shown).
[0047] 3) homogenization treatment: subjecting the as-cast composite material obtained in step 2) to a solution treatment at 200° C. for 12 h;
[0048] 4) Hot extrusion molding: The cast composite material after homogenization treatment in step 3) is preheated at 350°C for 1.0h, and then extruded at an extrusion temperature of 300°C, an extrusion ratio of 25:1, and an extrusion speed of 1m / s to obtain a titanium particle reinforced magnesium-based composite material.
[0049] The performance of the prepared magnesium-based composite material is tested in this application, wherein the metallographic diagram of the magnesium-based composite material is as follows: Figure 3 As shown in the figure, it can be seen that spherical titanium particles with a diameter of 5-10 μm can be distributed relatively evenly in the matrix without obvious agglomeration, which is beneficial to the improvement of the comprehensive mechanical properties of magnesium-based composites.
[0050] The present application also conducts mechanical property tests on the magnesium-based composite material. Specifically, at room temperature, the tensile mechanical properties of the magnesium-based composite material are measured, and the tensile strength is 223MPa, the yield strength is 153MPa, and the elongation is 18.8%. Compared with the mechanical properties of comparative example 1 at room temperature, the tensile strength, yield strength and elongation of the material are increased by -0.9%, -6.7% and 55.4%, respectively.
[0051] Comparative Example 1
[0052] This embodiment provides a method for preparing a titanium particle-reinforced magnesium-based composite material with good plasticity, which comprises the following steps:
[0053] 1) Preheating titanium particles: weigh 30 g of titanium particles with a particle size of ≤20 μm and put them into a crucible, and preheat them at 200° C. for 30 min;
[0054] 2) Liquid casting molding: In the presence of a mixed gas of carbon dioxide and sulfur hexafluoride in a mass ratio of 1:99, 1060g of pure magnesium is placed in a crucible and heated to 720°C. After melting, it is kept warm for 10 minutes; the temperature is lowered to 680°C, 30g of preheated titanium particles are added, and mechanical stirring is applied with a disc stirring paddle. The stirring paddle is not kept in a fixed position, and is stirred up and down in the solution at a speed of 600rad for 5 minutes; after the mechanical stirring is completed, the composite melt is heated to 680°C, and the preheated ultrasonic stirrer is placed in the composite melt. The ultrasonic stirring head is immersed 4-5cm from the liquid surface, the power is 150W, and the dispersion time is 10min; after the composite melt is evenly dispersed by ultrasound, it is immediately solidified by water cooling to obtain a cast composite material.
[0055] 3) homogenization treatment: subjecting the as-cast composite material obtained in step 2) to a solution treatment at 200° C. for 12 h;
[0056] 4) Hot extrusion molding: The cast composite material after the solution treatment in step 3) is preheated at 350°C for 1.0h, and then extruded at an extrusion temperature of 300°C, an extrusion ratio of 25:1, and an extrusion speed of 1m / s to obtain a titanium particle reinforced magnesium-based composite material.
[0057] The performance of the prepared magnesium-based composite material was tested in this application, wherein the SEM image of the magnesium-based composite material is as follows: Figure 1 As shown in the figure, it can be seen that spherical titanium particles with a diameter of 5-10 μm are evenly distributed along the extrusion direction, without obvious agglomeration, and there is a small amount of oxide around them.
[0058] The present application also conducts mechanical property tests on the magnesium-based composite material. Specifically, at room temperature, the tensile mechanical properties of the magnesium-based composite material are measured, and the tensile strength is 225 MPa, the yield strength is 164 MPa, and the elongation is 11.2%.
[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a titanium particle-reinforced magnesium-based composite material with good plasticity, characterized in that: The steps include: 1) Liquid casting: placing a magnesium substrate in a crucible, introducing a protective gas, heating to form a liquid magnesium melt, and keeping the temperature; quickly adding the preheated titanium particles into the liquid magnesium melt, stirring with a preheated shear force stirrer, and then quickly water cooling to obtain a cast composite material; 2) homogenization treatment: subjecting the as-cast composite material in step 1) to solution treatment at 150-250° C. for 6-18 h; 3) hot extrusion molding: preheating the cast composite material that has been homogenized in step 2) and then hot extruding it to obtain a magnesium-based composite material reinforced with titanium particles; Among them, in step 1), the preheated titanium particles are quickly added to the magnesium melt, and the stirring conditions of the preheated shear stirrer are: first, stir at a speed of 100-300 rpm, which is consistent with the speed of the stirring head, increase the speed to 1000-1400 rpm and stir for 4-10 minutes, and during the stirring process, the position of the stirring head in the magnesium melt is fixed, and the bottom end of the stirring head is 10-50 mm away from the bottom of the crucible.
2. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 1, characterized in that: The mass ratio of the magnesium matrix to the titanium particles is 97-99:1-3.
3. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 2, characterized in that: The temperature of the liquid magnesium melt is 680-730°C.
4. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 3, characterized in that: The particle size of the titanium particles is not greater than 20 μm.
5. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 4, characterized in that: The preheating parameters of the titanium particles are: preheating temperature is 200-300° C., and preheating time is 20-40 minutes.
6. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 5, characterized in that: The preheating conditions of the shear force agitator in step 1) are: preheating temperature is 600-700° C., and preheating time is 30-60 min.
7. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 1, characterized in that: The protective gas in step 1) is a mixed gas of carbon dioxide and sulfur hexafluoride in a mass ratio of 1:
99.
8. The method for preparing a titanium particle reinforced magnesium-based composite material with good plasticity according to claim 6, characterized in that: The extrusion molding conditions in step 3) are: preheating temperature of 300-400°C, preheating time of 0.5-1.5h, extrusion temperature of 280-400°C, extrusion ratio of 25:1, and extrusion speed of 0.5-1m / s.
9. A titanium particle reinforced magnesium-based composite material with good plasticity obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The magnesium-based composite material has a tensile strength of 220-230 MPa, a yield strength of 150-160 MPa, and an elongation of 18-25%.
Citation Information
Patent Citations
Liquid metal stirring device
CN214681162U
Cited By
Modular semi-solid forming method and system for particle-reinforced magnesium-based composite material
CN121373351A
Modular semi-solid forming method and system for particulate reinforced magnesium matrix composites
CN121373351B